Combined effects of bifurcation and magnetic field on the performance of phase change material installed cylinder with small inlet temperature perturbations during nanofluid convection - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2022)
In the present study, effects of bifurcation, magnetic field and perturbations in the inlet temperature on the phase change process dynamics are explored during hybrid nanofluid convection in a phase change material (PCM) filled cylinder. The study is conducted for different values of Reynolds number (Re number between 250 and 500), magnetic field strength (Ha number between 0 and 15), bifurcation location (yb between 0.1H2 and 0.3H2) and nanoparticle loading in the base fluid (between 0.02 % and 0.1 % ). The analysis are also performed for flat channel configurations. The perturbation levels for the inlet temperature are considered between 1 % and 5 % . The presence of bifurcation affects the main flow features while phase change become very slower as compared to flat channel case. At higher Re numbers phase change become fast for both channels while complete phase transition time (t-PC) reduces by about 73 % and 26 % for bifurcating and flat channels. The effect of magnetic field on the phase change dynamics behavior becomes opposite for flat and bifurcation channels. A 20 % reduction of t-PC is achieved for flat channel while it increases by about 146 % for bifurcating channel at the highest strength. The variation of t-PC becomes 6 % for nanoparticle loading at the highest amount and when varying the location of the bifurcation. The effects of inlet temperature perturbations on the phase change become significant for higher perturbations levels and lower inlet temperatures. A dynamic model is obtained using numerical experiments with different inlet temperatures and perturbation levels. (c) 2022 Elsevier Ltd. All rights reserved.
Keywords: Magnetic field; Bifurcation; Phase change dynamics; CFD; Perturbations; Nanofluid